2020
DOI: 10.2147/opth.s290125
|View full text |Cite
|
Sign up to set email alerts
|

<p>VRF-G, a New Intraocular Lens Power Calculation Formula: A 13-Formulas Comparison Study</p>

Abstract: Purpose To compare the accuracy of a newly developed intraocular lens (IOL) power formula (VRF-G) with twelve existing formulas (Barret Universal II, EVO 2.0, Haigis, Hill-RBF 2.0, Hoffer Q, Holladay 1, Kane, Næeser 2, PEARL-DGS, SRK/T, T2 and VRF). Methods Retrospective case series including 828 patients having uncomplicated cataract surgery with the implantation of a single IOL model (SN60WF). Using optimised constants, refraction prediction error of each formula was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
35
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 21 publications
2
35
0
2
Order By: Relevance
“…In our study, this formula confirmed its reputation remaining one of the most accurate formulas across the whole sample and in the long eyes subgroup. However, in short eyes, Barrett showed a lower accuracy achieving one of the highest MAE, MedAE (SD) at 0.300D, 0.249D (0.339), in agreement with previous studies[35, 15].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In our study, this formula confirmed its reputation remaining one of the most accurate formulas across the whole sample and in the long eyes subgroup. However, in short eyes, Barrett showed a lower accuracy achieving one of the highest MAE, MedAE (SD) at 0.300D, 0.249D (0.339), in agreement with previous studies[35, 15].…”
Section: Discussionsupporting
confidence: 92%
“…Kane had the lowest MAE and SD in the whole sample as well as the highest percentage of PE within ±0.50D and was proven to be more effective than old generation formulas like Hoffer Q and Haigis ( P < .001). Several studies have previously reported the same finding using PCI biometers[4, 12] or newer technologies[3, 5, 11, 15]. In fact, multiple articles have recently confirmed that Kane is the most accurate formula overall and in each axial length subgroup[4, 7, 10].…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“… 9 11 12 13 With the growing popularity, patients' refractive expectations after the cataract surgery continue to increase, and achieving the desired refractive outcome has become a key principle in recent years. 7 Identifying an IOL formula that best predicts the postoperative refractive outcome is one of the most important factors leading to a successful cataract surgery. Recently, newer generation of IOL formulas, which integrate artificial intelligence and larger number of preoperative eye parameters for prediction, have been introduced.…”
Section: Discussionmentioning
confidence: 99%
“… 6 Furthermore, some of the modern formulas, such as Hill-RBF and Kane, have incorporated the technology of adaptive learning from a large dataset to predict refractive outcomes. 3 7 …”
Section: Introductionmentioning
confidence: 99%